(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Since the start of the crisis in the Syrian Arab Republic suffered many universities and colleges affiliated facilities and higher education major damage, as the whereabouts of these universities in geographical areas where terrorist operations led to sabotage and exposed infrastructure of these universities and led in many places to transfer the headquarters of these universities and private universities from permanent places to temporary places to maintain the functioning of the educational process and to maintain the teaching staff and students in safe places far from conflict zones, and as a result of the transfer of the headquarters of most of the private universities to new temporary headquarters emerged as the importance of protecting the Giver T. These universities from loss and fraud, where these data include academic records for students and information teaching staff and teaching materials for colleges, where the biggest focus is to protect these data from plagiarism and fraud, which has emerged as a major problem as a result of these changes in the places of the universities. So the aim of this paper is to invest in technology in creating new and unique method to protect documents students’ academic from cybercrime and especially from plagiarism, fraud, change their records, as this innovative method uses the latest technology in encryption and protection of documents where use Quick Response Code is called abbreviated QR code. We’ll show in this paper how to use QR code in the protection of documents students and academic records and code will show the implementation of this method in ITTHAD private University. منذ بدء الأزمة في الجمهورية العربية السورية تعرضت العديد من الجامعات والكليات التابعة لها ومنشآت التعليم العالي لأضرار كبيرة، حيث أن مكان تواجد هذه الجامعات في مناطق جغرافية شهدت عمليات إرهابية أدى لتخريب وتعرض البنى التحتية لهذه الجامعات وأدى ذلك في العديد من الأماكن بنقل مقرات هذه الجامعات وخاصة الجامعات الخاصة من مقراتها الدائمة إلى مقرات مؤقتة للمحافظة على سير العملية التعليمية والإبقاء على الكادر التدريسي والطلبة في أماكن آمنة بعيدة عن مناطق النزاعات، ونتيجة لنقل مقرات أغلب الجامعات الخاصة إلى مقرات جديدة مؤقتة برزت أهمية حماية معطيات هذه الجامعات من الضياع والتزوير، حيث تشمل هذه المعطيات السجلات الأكاديمية للطلاب ومعلومات الكادر التدريسي و المواد التدريسية الخاصة بالكليات، حيث أن التركيز الأكبر هو حماية هذه المعطيات من الجرائم الالكترونية ومن التزوير الذي برز كمشكلة كبيرة نتيجة هذه التغييرات في مقرات الجامعات. لذا تهدف هذه الورقة العلمية لاستثمار التكنولوجيا في ابتكار طريقة فريدة وجديدة لحماية وثائق الطلاب وسجلاتهم الأكاديمية من أهم الجرائم الالكترونية وهي الانتحال والتزوير والتغيير، حيث أن هذه الطريقة المبتكرة تستخدم أحدث تقنية في التشفير وحماية الوثائق حيث تستخدم كود الاستجابة السريعة Quick Response Code ويدعى اختصاراً بـ QR code. سوف نعرض في هذه الورقة كيفية استخدام كود الاستجابة السريعة QR في حماية وثائق الطلاب وسجلاتهم الأكاديمية وسوف نعرض تطبيق هذه الطريقة في جامعة الاتحاد الخاصة.